Implementation of Internal Controls Over Inventory Based on COSO at CV. Enigma Pasifik Seafood - Afifatuz Zuhrah; Aqwa Naser Daulay; Kusmilawaty (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to evaluate the effectiveness of the implementation of an internal control system for inventory in a seafood processing company. The approach used in this study is a qualitative approach with an explanatory analysis design. The primary data in this study were collected through interviews and direct field observations, which were then analyzed using descriptive techniques based on the five components of the COSO Framework. Based on the study results, the implementation of internal control over inventory based on the COSO Framework approach is only 40.00% compliant overall, indicating a “not met” category. The results show that the compliant COSO components relate to Information and Communication. Risk Assessment is categorized as “sufficiently met.” However, Control Environment, Control Activities, and Monitoring Activities remain non-compliant. The failure to meet these components stems from a manual recording system, the absence of written standard operating procedures (SOPs), absences that are not formally documented, and the lack of periodic physical counts. These weaknesses result in inaccurate inventory records, causing them to lose their function as a decision-making tool for management. As a solution, the company is advised to implement daily Excel-based computerization, develop written SOPs, tighten authorization procedures, schedule inventory counts, and improve preventive oversight.